Isolation of a peptide containing d-amino acid residues that inhibits the α-helix-mediated p53–MDM2 interaction from a one-bead one-compound library. Issue 3 (1st February 2018) - Morimoto, Jumpei; Hosono, Yuki; Sando, Shinsuke
Graphical abstract: Abstract: α-Helix-mediated protein–protein interactions (PPIs) are important targets in biological research and drug development. Peptides containingd -amino acid residues are attractive molecules for inhibiting α-helix-mediated PPIs because of their wide surface area and high protease resistance. In this study, a peptide library was constructed using a one-bead one-compound format designed to isolate left-handed α-helical peptides, which are promising molecules as inhibitors of α-helix-mediated PPIs. Screening of the library against an α-helix-mediated PPI between MDM2 and p53 yielded an inhibitor of the PPI. Design and screening of the library, and biochemical and spectroscopic studies of the discovered peptide are presented.